Educational interventions for knowledge on the disease, treatment adherence and control of diabetes mellitus - Ana Laura Galhardo Figueira; Lilian Cristiane Gomes Villas Boas; Anna Claudia Martins Coelho; Maria Cristina Foss de Freitas; Ana Emilia Pace
Abstract Objective: to assess the effect of educational interventions for knowledge on the disease, medication treatment adherence and glycemic control of diabetes mellitus patients. Method: evaluation research with "before and after" design, developed in a sample of 82 type 2 diabetes mellitus patients. To collect the data, the Brazilian version of the Diabetes Knowledge Scale (DKN-A), the Measure of Adherence to Treatments and the electronic system at the place of study were used. The data were collected before and after the end of the educational interventions. The educational activities were developed within 12 months, mediated by the Diabetes Conversation Maps, using the Cognitive Social Theory to conduct the interventions. Results: the knowledge on the disease (p<0.001), the medication treatment (oral antidiabetics) (p=0.0318) and the glycated hemoglobin rates (p=0.0321) improved significantly. Conclusion: the educational interventions seem to have positively contributed to the participants' knowledge about diabetes mellitus, the medication treatment adherence and the glycated hemoglobin rates.